Data on low-molecular weight proteins of Escherichia coli treated by essential oils components, tetracycline, chlorine and peroxide by MALDI-TOF MS - Božik, Matěj; Cejnar, Pavel; Maršík, Petr; Klouček, Pavel (Data in brief, 2018)
In this dataset we provide MALDI-TOF MS spectra of Escherichia coli. The data presented in this article are related to the article entitled "Stress response of Escherichia coli to essential oil components - insights on low-molecular-weight proteins from MALDI-TOF" (Božik et al., 2018) [1]. Essential oils and their components are known for their antibacterial effect. Many studies evaluated the effect of essential oil components (EOCs) on the cell wall, bacterial membranes, and energetic metabolism. But data about low molecular weight proteins (<20 kDa) are limited. Provided data are focused on bacterial response to EOCs; tetracycline, peroxide and chlorine was used as control as common antibiotic and disinfectant agents used against bacteria. These data describe the effect of tested substances to bacterial protein synthesis.